Anti-smoking legislation and its effects on urinary cotinine and cadmium levels - Sánchez-Rodríguez, Jinny E.; Bartolomé, Mónica; Cañas, Ana I; Huetos, Olga; Navarro, Carmen; Rodríguez, A. Carolina; Arribas, Misericordia; Esteban, Marta; López, Ana; Castaño, Argelia (Environmental research, 2015)
Anti-smoking legislation has been associated with an improvement in health indicators. Since the cadmium (Cd) body burden in the general population is markedly increased by smoke exposure, we analyzed the impact of the more restrictive legislation that came into force in Spain in 2011 by measuring Cd and cotinine in first morning urine samples from 83 adults in Madrid (Spain) before (2010) and after (2011) introduction of this law. Individual pair-wise comparisons showed a reduction of creatinine corrected Cotinine and Cd levels for non-active smokers, i. e. those which urinary cotinine levels are below 50μg/L. After the application of the stricter law, cotinine levels in urine only decreased in non-active smokers who self-reported not to be exposed to second-hand smoke. The reduction in second hand smoke exposure was significantly higher in weekends (Friday to Sunday) than in working days (Monday to Thursday). The decrease in U-Cd was highly significant in non-active smokers and, in general, correlated with lower creatinine excretion. Therefore correction by creatinine could bias urinary Cd results, at least for cotinine levels higher than 500μg/L. The biochemical/toxicological benefits detected herein support the stricter application of anti-smoking legislation and emphasize the need to raise the awareness of the population as regards exposure at home.